Dependence on Criminal Judgement as the Civil Court’s Limit of Free Establishment of Facts – The Example of Hungarian Legal Practice - Pribula, László (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
Based on the free statement facts, the court, acting in a civil case, may freely use and evaluate the available evidence based on its conviction, without formal rules of evidence. Justified exceptions from the ground rule may be stated only in a restrained circle. For several decades, Hungarian procedural law has contained partial dependence on the judgment of a criminal court as one of these exceptions. The meeting point of two different legal areashas always had special importance. This study aims to review the challenges created by this exceptional dependence and the chief stages of the development of the law.